Prevalence and Factor Relating to Intestinal Protozoan : Sarcocystis hominis Infection among Thai, 2009 - Nichpanit, Somchai; Wongsaroj, Thitima; Nak -Ai, Worayuth (Journal of Health Science of Thailand, 2018)
Sarcocystis hominis was major cause of sarcocystosis and Human Hypereosinophilic Syndrome (HPS) and chronic diarrhea. The objective of this study was to analyze the variable of Sarcocystis hominis prevalence and factors that correlated with S. hominis infection among Thai people in Thailand. Methodological study was designed by using 30 cluster random sampling under World Health Organization guideline. A total of 15,555 samples of Thai people which represented the total population of Thailand were collected for this cross sectional study between February and June 2009. The result showed that the prevalence of Sarcocystis hominis among Thai was 1.5 percent and reportedly higher among male particularly in the 50-59 year age group and the highest in North East region. The significant influences correlating with Sarcocystis hominis infection were raw fresh beef consumption behavior, raw meat/meat product consumption behavior, contaminated vegetable consumption and defecating in unsanitary toilet (p < 0.05). The goodness of predicting Sarcocystis hominis infection raw beef consumption was 28.98 percent of prediction, an algebraic equation model to determine Sarcocystosis was (-7.079 + (1.268) (raw meat, uncooked beef consumption) + (1.831) uncooked spiced mince meat + (-1.297) (not defecate in toilet) In conclusion, Sarcocystis hominis, impacted on health, the transmission occurred among people with poor hygiene and unhygienic food consumption behavior.